Comparison of Measures of Ability in Adolescents with Intellectual Disability - Mungkhetklang, Chantanee; Crewther, Sheila G.; Bavin, Edith L.; Goharpey, Nahal; Parsons, Carl (Frontiers in Psychology, 2016)
Finding the most appropriate intelligence test for adolescents with Intellectual Disability (ID) is challenging given their limited language, attention, perceptual and motor skills and ability to stay on task. The study compared performance of 23 adolescents with ID on the Wechsler Intelligence Scale for Children-Fourth Edition (WISC-IV), one of the most widely used intelligence tests, and three nonverbal IQ tests, the Raven’s Coloured Progressive Matrices, the Test of Nonverbal Intelligence-Fourth Edition and the Wechsler Nonverbal test of Ability. Results showed that the WISC-IV Full Scale IQ raw and scaled scores were highly correlated with total scores from the three nonverbal tests, although the correlations were higher for raw scores, suggesting they may lead to better understanding of within group differences and what individuals with ID can do at the time of assessment. All participants attempted more questions on the nonverbal tests than the verbal. A preliminary analysis showed that adolescents with ID without ASD (n=15) achieved higher scores overall than those presenting with ID+ASD (n=8). Our findings support the view that short nonverbal tests are more likely to give a similar IQ result as obtained from the WISC-IV. In terms of the time to administer and the stress for participants, they are more appropriate for assessing adolescents with ID.